Edukacja akademicka w dobie sztucznej inteligencji = Academic education in the age of artificial intelligence - Jaworski, Krzysztof (1961- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article reflects on academic education in the age of dynamic development of artificial intelligence, analyzing its implications across three key dimensions of university functioning: teaching, research, and organization. The author draws on constructivist and transformative paradigms, Mitchell Resnick`s concept of creative learning, and the SAMR model, highlighting the potential of project-based work, autonomy, and the reflective use of digital technologies.
Keywords: edukacja akademicka; sztuczna inteligencja; uniwersytet; academic education; artificial intelligence; university